STAТIC ANALYSIS OF CROSS STEEL TRUSSES WITH A RECTANGULAR GRID OF COLUMNS - Alexander S. Marutyan (Современная наука и инновации, 2022)
The article presents a model for static analysis of cross structures on rectangular plans with different aspect ratios. The data are compared with the results of numerical and experimental research, including natural tests of experimental and industrial samples of block covering.